Detection of phishing websites based on the improved TrustRank algorithm - Hao HAN; Bowen LIU; Guoyuan LIN (Dianxin kexue)
Anti-phishing methods just generally detect phishing sites based on comparing the similarity of pages features,which could be anti-detected when attackers are clear about the extraction process of features.Therefore,a method based on web pages relationship was proposed to detect phishing websites.According to this method,phishing websites were detected by an improved TrustRank algorithm which set up a collection of web pages and used the link relationship between phishing websites and other websites.Experiments show that the improved TrustRank algorithm can focus the trust values of phishing websites on some range with the lower false positive rate,the lower false negative rate and the higher speed compared to other methods.